136k views
0 votes
Which is the simplified form of the expression

Which is the simplified form of the expression-example-1

2 Answers

5 votes

Answer:

B. 1/(x^21y^12)

Explanation:

First solve of x:

x^-3 / x^4 is same thing as 1/ x^3x^4 which is equal to 1/x^7

Now the cube part: (1/x^7)^3 = 1/x^21

Solve for y:

y^2 / y^6

1/ y^-2y^6 = 1/y^4

(1/y^4)^3

1/y^12

Answer: 1/(x^21y^12)

User RichardCook
by
5.0k points
5 votes

Answer:

B)
(1)/(x^(21) y^(12) )

Explanation:

The given expression is
(((x^(-3) (y^(2)) )/(x^4 y^6) )^3

Now we can bring the power 3 inside the bracket using the rule
(a^(m) )^n = a^(mn)

=
(x^(-9)(y^6) )/(x^(12)y^(18)  )

Now we have to use the quotient rule and simplify it.


(a^m)/(a^n) = a^(m-n)

Using the above rule, we get

=
x^(-9 -12) *y^(6-18)

=
x^(-21) *y^(-12)

Since we have a negative exponent. We can rewrite using the rule a^-m = 1/a^m

=
(1)/(x^(21) y^(12) )

Therefore the answer is B)
(1)/(x^(21) y^(12) )

User Rothloup
by
4.3k points